A Giant Left Atrial Appendage Aneurysm With Incessant Atrial Tachycardia - Wei, Hui‐Qiang; Xue, Yumei; Wu, Shulin; Liao, Hongtao (Journal of cardiovascular electrophysiology, 2025)
ABSTRACT Introduction Left atrial appendage aneurysm (LAAA) is a rare congenital cardiac anomaly that involves the progressive dilatation of the left atrial appendage (LAA), predisposing the patient to serious complications such as atrial tachyarrhythmias, life‐threatening systemic thromboembolism, and cardiac dysfunction. Methods and Results We described a case of a 36‐year‐old woman with incessant atrial tachycardia (AT) originating from LAAA, which surgical intervention successfully terminated AT after attempted ablation failed. The AT terminated after the LAA was excised. There was no recurrence at the follow‐up period of 3 months. Conclusion We present and discuss the management of rare incessant AT arising from giant LAAA where the localization was confirmed on electroanatomic mapping. LAA resection via video‐assisted thoracoscopic surgery is minimally invasive approach to manage the LAAA AT, uniformly considered safe and successful.